Femoral Neck Nonunion Associated With Delayed Union of Ipsilateral Femoral Shaft Fracture - Santoshi, John A (Cureus, 2021)
We report the case of a 36-year-old man, who presented to us five months after the initial trauma. He had been treated elsewhere with a cephalomedullary femoral nail. He described severe pain in his right thigh and groin that confined him to a wheelchair. He had shortening of the right lower limb and painful restriction of movements of the right hip. Radiographs demonstrated hypertrophic callus with a gap at the femoral shaft while the neck fracture was in varus malalignment with bone resorption; the neck fracture been fixed using two hip screws that were missing the nail. The patient was managed with removal of the previous hardware, reamed retrograde nailing and Pauwels’ intertrochanteric valgus osteotomy fixed using a 120(o) double-angled condylar blade plate. Both the fracture sites were not opened. Postoperatively, the femoral shaft showed radiographic evidence of union at three months, while the femoral neck and the intertrochanteric osteotomy site had united at five months. As per the Friedman and Wyman criteria, our patient has a “good” outcome at the four-year follow-up.